Prospective comparison of transient, point shear wave, and magnetic resonance elastography for staging liver fibrosis - Lefebvre, Thierry; Wartelle-Bladou, Claire; Wong, Philip; Sebastiani, Giada; Giard, Jeanne-Marie; Castel, Hélène; Murphy-Lavallée, Jessica; Olivié, Damien; Ilinca, André; Sylvestre, Marie-Pierre; Gilbert, Guillaume; Gao, Zu-Hua; et al. (European radiology, 2019)
Objectives To perform head-to-head comparisons of the feasibility and diagnostic performance of transient elastography (TE), point shear-wave elastography (pSWE), and magnetic resonance elastography (MRE). Methods This prospective, cross-sectional, dual-center imaging study included 100 patients with known or suspected chronic liver disease caused by hepatitis B or C virus, nonalcoholic fatty liver disease, or autoimmune hepatitis identified between 2014 and 2018. Liver stiffness measured with the three elastographic techniques was obtained within 6 weeks of a liver biopsy. Confounding effects of inflammation and steatosis on association between fibrosis and liver stiffness were assessed. Obuchowski scores and AUCs for staging fibrosis were evaluated and the latter were compared using the DeLong method. Results TE, pSWE, and MRE were technically feasible and reliable in 92%, 79%, and 91% subjects, respectively. At univariate analysis, liver stiffness measured by all techniques increased with fibrosis stages and inflammation and decreased with steatosis. For classification of dichotomized fibrosis stages, the AUCs were significantly higher for distinguishing stages F0 vs. ≥ F1 with MRE than with TE (0.88 vs. 0.71; p < 0.05) or pSWE (0.88 vs. 0.73; p < 0.05), and for distinguishing stages ≤ F1 vs. ≥ F2 with MRE than with TE (0.85 vs. 0.75; p < 0.05). TE, pSWE, and MRE Obuchowski scores for staging fibrosis stages were respectively 0.89 (95% CI 0.85–0.93), 0.90 (95% CI 0.85–0.94), and 0.94 (95% CI 0.91–0.96). Conclusion MRE provided a higher diagnostic performance than TE and pSWE for staging early stages of liver fibrosis. Trial registration NCT02044523 Key Points • The technical failure rate was similar between MRE and US-based elastography techniques. • Liver stiffness measured by MRE and US-based elastography techniques increased with fibrosis stages and inflammation and decreased with steatosis. • MRE provided a diagnostic accuracy higher than US-based elastography techniques for staging of early stages of histology-determined liver fibrosis.